2001
DOI: 10.1029/2001jb000373
|View full text |Cite
|
Sign up to set email alerts
|

Submersible study of an oceanic megamullion in the central North Atlantic

Abstract: Abstract. Recently discovered megamullions on the seafloor have been interpreted to be the exhumed footwalls of long-lived detachment faults operating near the ends of spreading segments in slow spreading crust. We conducted five submersible dives on one of these features just east of the rift valley in the Mid-Atlantic Ridge at 26ø35'N and obtained visual, rock sample, gravity, and heat flow data along a transect from the breakaway zone (where the fault is interpreted to have first nucleated in -2.0-2.2 Ma cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
104
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 77 publications
(114 citation statements)
references
References 52 publications
8
104
0
2
Order By: Relevance
“…[4] Prior processing of bathymetry and gravity data in this region [Blackman et al, 1998;Nooner et al, 2003] and at other OCCs [Cannat et al, 2006;Fujiwara et al, 2003;Okino et al, 2004;Searle et al, 2003;Tucholke et al, 2001] indicates that the shallow domes are not locally compensated, each being associated with a positive mantle Bouguer gravity anomaly. However, care should be taken in using mantle Bouguer anomalies to investigate subsurface density structure in the vicinity of OCCs.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Prior processing of bathymetry and gravity data in this region [Blackman et al, 1998;Nooner et al, 2003] and at other OCCs [Cannat et al, 2006;Fujiwara et al, 2003;Okino et al, 2004;Searle et al, 2003;Tucholke et al, 2001] indicates that the shallow domes are not locally compensated, each being associated with a positive mantle Bouguer gravity anomaly. However, care should be taken in using mantle Bouguer anomalies to investigate subsurface density structure in the vicinity of OCCs.…”
Section: Introductionmentioning
confidence: 99%
“…The origin of the corrugations is still enigmatic. Direct observations have shown that they are not produced by faults parallel to the spreading direction 14,19 . One possibility is that they originate by continuous casting 20 of a ductile footwall by irregularities in a strong and brittle hanging wall.…”
mentioning
confidence: 99%
“…Essa cadeia foi interpretada como um megamullion, que foi deformado, posteriormente, por tectonismo recente Sichel et al, 2009). O megamullion, chamado também de mantle core complex, é a saliência morfológica abissal na forma de carapaça de tartaruga constituída por rochas ultramáficas do manto abissal (Figura 6A; Tucholke et al, 2001). Além das rochas ultramáficas, ocorre uma quantidade significativa de gabro.…”
Section: Morfologia Submarinaunclassified